Persistent Organic Pollutants - Kudom Donyinah, Stephen (IntechOpen, 2019)
This book consists of four technical articles and an introduction that discusses the characteristics of persistent organic pollutant (POP) behavior, covering organic matter in lake sediments, degradation pathways of POPs and specific pesticides, and the adaptation mechanisms of bacteria. The contributing articles are from authors with different backgrounds and specialties from reputable organizations and institutions. The book analyzes the effects of POPs and their characteristic behavior in different environments. Readers will hopefully gain interesting knowledge from this book.